Compatibility of materials with hydrogen. Particular case: Hydrogen embrittlement of titanium alloys - Madina, V.; Azkarate, I. (International journal of hydrogen energy, 2009)
A review of the effect of hydrogen on materials is addressed in this paper. General aspects of the interaction of hydrogen and materials, hydrogen embrittlement, low temperature effects, material suitability for hydrogen service and materials testing are the main subjects considered in the first part of the paper. As a particular case of the effect of hydrogen in materials, the hydride formation of titanium alloys is considered. Hydrogen absorption and the possible associated problems must be taken into account when considering titanium as a candidate material for high responsibility applications. The sensitivity of three different titanium alloys to the Hydrogen Assisted Stress Cracking phenomena has been studied by means of the Slow Strain Rate Technique (SSRT). The testing media have been sea water and hydrogen has been produced on the specimen surface during the test by cathodic polarization. Tested specimens have been characterized by metallography and scanning electron microscopy. Results obtained show that the microstructure of the materials, particularly the β-phase content, plays an important role on the sensitivity of the studied alloys to the Hydrogen Assisted Stress Cracking Phenomena.